2016
DOI: 10.1007/s40265-016-0642-8
|View full text |Cite
|
Sign up to set email alerts
|

Drug Treatment of Hypertension: Focus on Vascular Health

Abstract: Hypertension, the most common preventable risk factor for cardiovascular disease and death, is a growing health burden. Serious cardiovascular complications result from target organ damage including cerebrovascular disease, heart failure, ischaemic heart disease and renal failure. While many systems contribute to blood pressure elevation, the vascular system is particularly important, because vascular dysfunction is a cause and consequence of hypertension. Hypertension is characterised by a vascular phenotype … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
45
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 217 publications
(242 reference statements)
2
45
0
8
Order By: Relevance
“…In turn, these can contribute to enhancements in AI and further increases in aortic BP, indicating a vicious cycle, in which the microcirculation maintains or even amplifies an initial increase in BP. 46 In accordance, our data show for the first time, an inverse correlation between the magnitude of the hyperemic response within skeletal muscle microvessels and muscle oxygenation with aortic systolic and PP and AI%, suggesting a link between arterial stiffness and microvascular dysfunction with limitations in in vivo skeletal muscle oxygenation early in hypertension.In our newly diagnosed patients with hypertension, the more apparent reductions in muscle oxidative capacity indices than alterations in microvascular reactivity suggest an early role of skeletal muscle mitochondrial dysfunction in the pathogenesis of hypertension. In agreement, a study in spontaneously hypertensive rats showed that alterations in mitochondrial enzymes in cardiac muscle preceded the clinical manifestation of hypertension.…”
supporting
confidence: 89%
See 4 more Smart Citations
“…In turn, these can contribute to enhancements in AI and further increases in aortic BP, indicating a vicious cycle, in which the microcirculation maintains or even amplifies an initial increase in BP. 46 In accordance, our data show for the first time, an inverse correlation between the magnitude of the hyperemic response within skeletal muscle microvessels and muscle oxygenation with aortic systolic and PP and AI%, suggesting a link between arterial stiffness and microvascular dysfunction with limitations in in vivo skeletal muscle oxygenation early in hypertension.In our newly diagnosed patients with hypertension, the more apparent reductions in muscle oxidative capacity indices than alterations in microvascular reactivity suggest an early role of skeletal muscle mitochondrial dysfunction in the pathogenesis of hypertension. In agreement, a study in spontaneously hypertensive rats showed that alterations in mitochondrial enzymes in cardiac muscle preceded the clinical manifestation of hypertension.…”
supporting
confidence: 89%
“…44,45 In hypertension, the vascular phenotype is characterized by reduced compliance, elasticity/distensibility, and increased stiffness. 46 With increased stiffness in large vessels, the pulsatile pressure/flow of the left ventricular ejection (which is normally transformed in a continuous flow) moves downstream to the small vessels of the arterial tree. 46,47 The chronic increase in BP along with the mechanical stress on the vascular wall and inflammation are postulated to induce remodeling of the muscular vessel wall, mainly in small arterioles, but also in precapillary resistance vessels, leading to luminal restrictions and capillary rarefaction.…”
Section: Muscle Oxidative Capacity and Microvascular Reactivitymentioning
confidence: 99%
See 3 more Smart Citations